Interpretasi Terhadap Keistimewaan Manusia Dari Binatang Ciptaan Tuhan - Sofiana Desraini Wau, Sofiana; Syutriska Kardia Gulo; Yauidi Santos Santoso (PASOLO: Jurnal Ilmu Teologi dan Pendidikan Kristen, 2025)
This article examines the interpretation of human exceptionalism from a Christian perspective and critically approaches this concept. This article examines the Christian view of the relationship between humans and animals in the context of God's creation and considers how this view influences our understanding of human exceptionalism. Through analysis of biblical texts and Christian theological perspectives, this article explores the idea that humans were created by God as special creatures who were given the responsibility to care for the universe and live a right relationship with the Creator. However, in exploring this concept, this article also considers critical perspectives on the concept of human exceptionalism, including how this concept is understood in the context of evolution and modern scientific research. In addition, this article discusses the ethical implications of the concept of human exceptionalism, such as human responsibility towards environmental protection and animal welfare. This article uses a critical approach to explore the complexity of the Christian view of human exceptionalism and how this view can contribute to a deeper understanding of the relationships between humans, animals, and their Creator.